DIMENSI SOSIAL DAN SPIRITUAL IBADAH ZAKAT - Karim, Abdul (ZISWAF, 2015)
urely Allah commands Zakat is not just carried out according to the size and content of its provisions to the people who deserve (mustahiq), but more than just obligations to be implemented. Zakat is not only a divine dimension (hablum minallah) but also has a social dimension of humanity (hablum minannas). Therefore charity is a necessity indeed a servant of God who gifted fortune to share with his fellow creatures. Commandments of zakat in the Qur’an has a very profound message of social sensitivity of humanity as well as foster the spiritual values that can shape the character of humanity filled with concern for the environment. With a Muslim charity will be met in a tangle of Islamic brotherhood is a close, and with zakat, a man believed to have a more worldly perspective ascetic (ascetic) that makes a person no longer has the heart to the world’s dependence excessive, so be a better person thanks and happy in various situations and conditions.Keywords : Zakat, Mustahiq, social dimension